TATHAWUR TA'LIM AL-LUGHAH AL-'ARABIYAH FI MA'HAD DARUL QUR'AN AL-ANWARIYAH BI MALUKU AL-WUSTHA - Sarah N Latuconsina (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
The teaching of Arabic at the Dar Al-Qur'an Al-Anwar Institute has been began at the Holy Quran Education Center in Tulio, Central Maluku since 1963, until it moved to the Institute of the Anwar Al-Quran in 2001 until now. There is an absolute evolution in the teaching of the Arabic language from time to time. There is an evolution in the teaching of the Arabic language from the first structure of the garden teaching the Quran,